高维空间上AB-渗流模型的一个引理(A lemma on AB-percolation models in high dimension) - SUZhong-gen(苏中根) (Zhejiang da xue xue bao. Journal of Zhejiang University. Sciences edition. Li xue ban, 2000)
This note gived another proof of asymptotic behaviors for AB-percolation model in Zd as d goes to infinity.The basic idea was to establish a relation between AB-percolation model in Zd and the classical percolation in V2 (one of partition sets of Zd),which particularly shows that the critical probability of AB-percolation in Zd is asymptotically the same as that of classical percolation in V2.